Rational Bubbles in the Real Housing Stock Market: Empirical Evidence from Santiago de Chile - Dettoni-Hidalgo, R (Elsevier Ltd, 2019)
In this paper we study the presence of rational bubbles in the IGP and IAR real housing stock indexes of Chile during the period 2003:01 to 2016:03 using a methodology based on fractionally integrated and cointegrated processes. Our findings suggest strong evidence in favour of bubbles in the Chilean housing stock market when no breaks are taken into account. Testing for structural breaks, three break dates are detected at 2007, 2011 and 2014, and the same evidence in favour of bubbles holds. This can be explained by the high level of debt of the Chilean people. © 2019 Elsevier B.V.